SOLUTION OF TRANSMISSION FUNCTIONS IN KINEMATICS - LABASOVA, Eva (Trends in education, 2008)
Computational problems of mechanics and dynamics of machines require to solve larger equations system, complex integrals, derivations and generation of graphical interdependency of parameters. Due to large time required to compute the integrated analytical or numerical solution tasks their solution is provided by students on self-access base at home. Application of computers and of proper mathematical codes it is possible to complete the solution of certain tasks within the teaching process. Utilization of computer algebra system Mathematica within the subject of solid mechanics to solve the transmission functions in mechanisms is described in the presented paper.
Keywords: upstroke dependence; transmission function; mechanism